2021
DOI: 10.1016/j.jbc.2021.100803
|View full text |Cite
|
Sign up to set email alerts
|

CSE1L promotes nuclear accumulation of transcriptional coactivator TAZ and enhances invasiveness of human cancer cells

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…In comparison, when individually depleting the other karyopherin-β type NTRs involved in import, including two of the three biportins, or the full set of importin α subtypes, only a slight reduction of YAP and TAZ nuclear localization was observable upon elimination of importin αs KPNA1, KPNA2, and KPNA7. This is consistent with earlier reports [45,157] implicating these importin α subtypes in YAP nuclear localization based on observed interactions (Section 3.2). Intriguingly, YAP, in return, controlled localization and function of importin 7: depletion of YAP or inhibition of the importin 7-YAP interaction by mechanical cues decreased importin 7 nuclear localization, whereas the MST1/2 inhibitor XMU-MP-1 had the opposite effect.…”
Section: Yap/yorkie Nuclear Import By a Karyopherin-β Type Ntrsupporting
confidence: 93%
See 1 more Smart Citation
“…In comparison, when individually depleting the other karyopherin-β type NTRs involved in import, including two of the three biportins, or the full set of importin α subtypes, only a slight reduction of YAP and TAZ nuclear localization was observable upon elimination of importin αs KPNA1, KPNA2, and KPNA7. This is consistent with earlier reports [45,157] implicating these importin α subtypes in YAP nuclear localization based on observed interactions (Section 3.2). Intriguingly, YAP, in return, controlled localization and function of importin 7: depletion of YAP or inhibition of the importin 7-YAP interaction by mechanical cues decreased importin 7 nuclear localization, whereas the MST1/2 inhibitor XMU-MP-1 had the opposite effect.…”
Section: Yap/yorkie Nuclear Import By a Karyopherin-β Type Ntrsupporting
confidence: 93%
“…The possibility of a direct involvement of classic import components in YAP/TAZ uptake was raised by pharmacological studies. Nagashima et al [157] found that a TAZ inhibitor, named TI-4, potently abrogated the nuclear accumulation of TAZ without affecting its phosphorylation. Searching for the underlying mechanism of this Hippo-independent effect, they identified CSE1L (exportin-2) as the major target of TI-4.…”
Section: Yap/taz-import Involving Importin α 331 Cse1l/importin αmentioning
confidence: 99%
“…RANBP17 biological network integration analysis found that XPO6, TNPO2, IPO9, XPO7, TNPO1, CSE1L have 3 functions. As of this time, XPO6, TNPO2, IPO9, XPO7, TNPO1 has not been reported in GBM, while CSE1L which is known to be involved in the recycling of importin α and as a biomarker of cancer malignancy, including formation, motility, and invasiveness [52]. Besides, we found 8 core upstream miRNA interact with RANBP17.…”
Section: Discussionmentioning
confidence: 67%
“…CSE1L overexpression was previously found to associate with the progression of a number of gastrointestinal cancers, including esophageal cancer, gastric cancer, hepatocellular carcinoma and CRC ( 1 , 2 , 44 , 45 ). Furthermore, CSE1L can promotes the nuclear distribution of the transcriptional coactivator with PDZ-binding motif to enhance the malignancy of human cancer tissues from osteosarcoma, glioma and lung cancer ( 46 ). Therefore, understanding the molecular mechanism underlying the effects of CSE1L may facilitate the optimization of cancer therapy ( 47 ).…”
Section: Discussionmentioning
confidence: 99%